2021
DOI: 10.1016/j.hrtlng.2021.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Does COVID-19 pneumonia signify secondary organizing pneumonia?: A narrative review comparing the similarities between these two distinct entities

Abstract: Multiple observational studies have described the similarities between COVID-19 pneumonia and organizing pneumonia (OP). These two entities clinically manifest with mild and subacute respiratory symptoms, often with a delayed diagnosis due to the atypical ARDS and silent hypoxemia presentation. Radiological features are often indistinguishable between the two. With the increase in antemortem lung biopsies and autopsies being performed, more histopathological findings of OP and its variant, acute fibrinous and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 89 publications
1
33
0
1
Order By: Relevance
“…Increased corticosteroid doses and treatment duration beyond the usual 10-day course are both recommended to establish remission and avoid relapse. Consistent evidence supports examining secondary OP in persons with past COVID-19 infection who have clinical and radiographic deterioration following recent cessation of corticosteroids, in the absence of evidence of new infection or other causation [ 3 , 11 ]. Secondary OP was a strong possibility in our patient.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Increased corticosteroid doses and treatment duration beyond the usual 10-day course are both recommended to establish remission and avoid relapse. Consistent evidence supports examining secondary OP in persons with past COVID-19 infection who have clinical and radiographic deterioration following recent cessation of corticosteroids, in the absence of evidence of new infection or other causation [ 3 , 11 ]. Secondary OP was a strong possibility in our patient.…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, Myall et al [ 10 ] reported that 39% of COVID-19 patients had persistent signs and symptoms 4 weeks following discharge. Interstitial lung illness, most often organizing pneumonia [ 3 ], was detected in 35 survivors (4.8%). On imaging, the majority of X-ray or computed tomography images revealed bilateral subpleural ground-class consolidation in the lower or middle section of the lung, or occasionally subpleural and peri-bronchial linear dense consolidation, as well as traction bronchiectasis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations